THE MAIN CHARACTER’S DEPRESSIVE SYMPTOMPS AS A CONSEQUENCE OF GENDER DISCRIMINATION DEPICTED IN “KIM JI-YOUNG, BORN 1982” - Istiqamah, Diyah; Abdullah, Abdullah (Faculty of Languages and Literature, Universitas Negeri Makassar, 2022)
For a long time, women have been subjected to gender-based discrimination. Discrimination seems more severe in a patriarchal culture because of the widespread belief in patriarchal norms. Some people have mental health concerns as a result of these gender biases. Literature, a mirror of society, is well-suited to addressing social concerns such as gender inequality. The aims of this research is to analyze the gender discrimination reflected in the novel “Kim JiYoung, Born 1982” by using Pilcher & Whelehan’s (2004) theory and how it affects the main character’s mental health using Beck’s (2009) theory. This research was conducted using a descriptive qualitative method and analyzed using a feminist approach. This research showed that Ji-Young undergone discrimination both in the private sphere as a daughter and a wife and within the public sphere as a student and an employee. Moreover, as a result of her experiences with discrimination on the based on gender, she started to show depressive symptoms which are; emotional manifestation, cognitive Manifestation, vegetative and physical manifestation, and hallucination as a stress response. This research concluded that Kim Ji-Young received gender discrimination in every phase of her life and as stress responses she started to emerge some symptoms of cognitive depression.